2018
DOI: 10.1039/c7ra13026k
|View full text |Cite
|
Sign up to set email alerts
|

Nafion®-coated mesoporous Pd film toward remarkably enhanced detection of lactic acid

Abstract: Mesoporous metal films can detect biomarkers with high sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Naon layer is critical to remove interferents present in sweat. 27 Next, three mL of 5% chitosan solution in 3% acetic acid was cast and the electrode was le overnight at 4 C. Following, we dropped 2 mL of GOx (10 mg mL À1 ) on the working electrode surface to dry for two hours and dropped 3 mL of 5% chitosan solution in 3% acetic acid. Finally, 2 mL of Naon (Naon : ethanol ¼ 1 : 10) were drop-casted on the working electrode surface to dry and stored at 4 C for standby.…”
Section: Electrode Modicationmentioning
confidence: 99%
“…Naon layer is critical to remove interferents present in sweat. 27 Next, three mL of 5% chitosan solution in 3% acetic acid was cast and the electrode was le overnight at 4 C. Following, we dropped 2 mL of GOx (10 mg mL À1 ) on the working electrode surface to dry for two hours and dropped 3 mL of 5% chitosan solution in 3% acetic acid. Finally, 2 mL of Naon (Naon : ethanol ¼ 1 : 10) were drop-casted on the working electrode surface to dry and stored at 4 C for standby.…”
Section: Electrode Modicationmentioning
confidence: 99%
“…Baba et al [ 113 ] reported a sensor based on porous palladium film, which when used in conjunction with a Nafion membrane produced selective detection for lactate. However, these were not tested in a sweat solution and had a smaller linear range than required for a clinical setting.…”
Section: Current Non-invasive Technology For Lactate Measurements mentioning
confidence: 99%
“…In another study, a hybrid composite of NiO NPs, PANI, and GO was deposited onto GCE using a two-step process [224]. Aniline and GO were mixed and coated on the surface of GCE followed by NiO NPs electrodeposition on aniline/GO/GCE in NiCl2 solution using a chronoamperometric process, which polymerized the aniline and deposited NiO NPs [249]; graphene embedded in a bowl-shaped PPy microcontainer was used for dopamine detection [250], Pt-incorporated fullerene-like ZnO nanospheres deposited onto GCE was used for cholesterol detection [251], Au NPs-rGO deposited onto GCE was used for determination of methylmercury (CH3Hg + ) in fish [252], and many more [253][254][255][256]. Notably, the direct electrodeposition of composite nanomaterials has been preferred for realizing the high conductivity and synergistic effect between the composite materials for biosensing applications.…”
Section: Electrochemical Depositionmentioning
confidence: 99%
“…To fabricate highly selective and sensitive glucose biosensors, GOx was immobilized on electrochemically deposited nanostructures, which presented excellent sensing performance during glucose detection[234][235][236][237][238][239][240]. However, the stability of such biosensors remains challenging due to the use of enzymes.In addition, electrochemically deposited nanomaterials onto electrode surfaces were used for a variety of biosensor applications[241][242][243][244][245][246][247][248][249][250][251][252][253][254][255][256]. For instance, electrochemical co-deposited cytochrome c and vertically aligned rGO onto GCE were used for H2O2 and Au nanostructures deposited onto an FTO substrate was used for Escherichia coli detection[245]; a two-dimensional (2D) MoS2 nanosheet onto Au-coated was used for nonesterified fatty acid biomarker monitoring[246]; iron terephthalate SPEs metal-organic framework onto GCE was used for H2O2 and nitrite detection[247]; cubic Cu2O nanocages loaded with Au NPs onto GCE was used for thrombin detection [248]; Nafion-coated mesoporous Pd film onto an Au substrate was used for detection of lactic acid…”
mentioning
confidence: 99%